마황(麻黃)의 기도과민반응의 효과 - 이성철; Seong Cheol Lee; 박성주; Sung Joo Park; 서상완; Sang Wan Seo; 황상욱; Sang Wook Hwang; 김영우; Yong Woo Kim; 송달수; Dal Soo Song; et al. (大韓本草學會誌, 2005)
Objectives : HERBA EPHEDRAE (HE) has been used cough and asthma for long time in korea. In the present study, we examined the effect HE on the ovalbumin (OVA)-induced airway hyper-reactivity (AHR). Methods : To examine the effect of HE on AHR, mice were sensitized with 100 mg of OVA and 1mg of alum intraperitoneally on day 0 and 14. On day 28, mice were challenged on 3 consecutive days with 3% OVA and AHR was assessed 24 h after the last challenge. To examine severity of airway hyper-reactivity, we examined eosinophil population and cytokine production in bronchoaveloar lavage fluid(BALF) and stained with hematoxylin and eosin in lung. Results : HE potently inhibited the development of airway hyper-reactivity and also reduced the number of eosinophil during OVA-induced airway hyper-reactivity. HE also inhibited cytokines production such as IL-4, IL-5, IL-13 in BALF. Furthermore, HE inhibited proliferation of eosinophil in a dose dependent manner. Conclusions : These results suggest that HE may be beneficial oriental medicine for AHR.